2010
DOI: 10.1097/psy.0b013e3181f6934f
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial Factors in the Development of Heart Disease in Women: Current Research and Future Directions

Abstract: Objective-To review the recent (1995)(1996)(1997)(1998)(1999)(2000)(2001)(2002)(2003)(2004)(2005)(2006)(2007)(2008)(2009)) literature on psychosocial risk and protective factors for coronary heart disease (CHD) among women, including negative emotions, stress, social relationships, and positive psychological factors.Methods-Articles for the review were identified using PubMed and bibliographies of relevant articles. Eligible studies included at least 100 women and either focused on (a) exclusively female parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
113
0
19

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 172 publications
(137 citation statements)
references
References 128 publications
5
113
0
19
Order By: Relevance
“…Women are traditionally more engaged in informal caregiving than men, and it has been suggested that women may be especially vulnerable to the joint health effects of demanding work and life circumstances (27,28). Furthermore, women in general still carry the largest household workload, and it has been shown that women have higher evening cortisol levels than men (29), indicating that they may have difficulties relaxing and unwinding after work.…”
mentioning
confidence: 99%
“…Women are traditionally more engaged in informal caregiving than men, and it has been suggested that women may be especially vulnerable to the joint health effects of demanding work and life circumstances (27,28). Furthermore, women in general still carry the largest household workload, and it has been shown that women have higher evening cortisol levels than men (29), indicating that they may have difficulties relaxing and unwinding after work.…”
mentioning
confidence: 99%
“…Bei Frauen, die bereits kardial erkrankt sind, scheint die Arbeitsbelastung allein nicht im Zusammenhang mit weiteren kardialen Ereignissen zu stehen [17]. Durch die Doppelbelastung durch Arbeitsbelastung und Eheprobleme wird ein erneutes kardiales Ereignis jedoch deutlich wahrscheinlicher als ohne diese Belastungen [9].…”
Section: Genderspezifische Aspekte Psychosozialer Risikofaktorenunclassified
“…Ebenso verschlechtert sich die Prognose von Patienten mit bestehender KHK, wenn sie sich als feindselig beschreiben [31]. Hier scheint es keine geschlechtsspezifischen Unterschiede zu geben [17].…”
Section: Genderspezifische Aspekte Psychosozialer Risikofaktorenunclassified
“…Dalla bibliografica una conferma evidente riguarda sicuramente la relazione diretta fra depressione e cardiopatia ischemica nelle donne [9,10,11,12,13], ma anche l'ansia [13], soprattutto nelle donne di mezza età, è in grado di incrementare il rischio di morte per tutte le cause cardiache del 77% [14]. Mentre un atteggiamento di ottimismo nelle donne risulta essere un fattore protettivo riducendo del 16% il rischio di infarto miocardio (IM), del 30% per mortalità relativa a cardiopatia ischemica (CHD) e del 24% per mortalità relativa a malattie cardiovascolari (MCV) [15].…”
Section: Introduzioneunclassified